A latecomer firm's R&D collaboration with advanced country universities and research institutes: The case of Huawei in Germany. (August 2019) - Liefner, Ingo; Si, Yue-fang; Schäfer, Kerstin
Abstract: Innovative latecomer firms are frequently examined for their international knowledge-seeking behavior and approaches towards fast technological learning. Within this line of research, however, little attention has been paid to latecomer firms' collaborative R&D with universities and research institutes (URI) in advanced economies. This paper examines the case of Huawei's collaborative R&D activities with German URI. It finds that in this latecomer case, the aims and the organization of collaboration differ markedly from the standard assumptions regarding university-industry collaboration with established firms: Huawei's collaborative R&D projects are aimed at fast and unidirectional technology absorption, involve a high degree of control and do not seek long-term personal interaction. The manifestation of these characteristics, however, changes over time. With these findings, this paper adds a new perspective to the literature on university-industry collaboration and to the literature on latecomer firms' knowledge-seeking behavior. Highlights: The paper extends the theoretical understanding of latecomer firms regarding their ways to absorb technology. Latecomer firms' university-industry-collaboration (UIC) differs from that of leading firms. Latecomer firms' UIC with advanced partners seeks to absorb pre-defined portions of technology. The preferred organization form for such a UIC is short-term contract research. Technological advancement of the latecomers induces a shift towards long-term collaboration.